ANALISIS POLA HIDUP KONSUMTIF MASYARAKAT NELAYAN DI KECAMATAN PANAI HILIR KABUPATEN LABUHANBATU (Analysis Consumtive Lifestyle of Fishermen Communities in the District of Panai Hilir, Labuhanbatu Regency) - Nina Safriyanti; Pindi Patana; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
This study aims to determine consumptive lifestyle of fishermen communities in District of Panai Hilir, Labuhanbatu Regency, Province of North Sumatra it also determined factors that cause consumptive behaviour and problem solving to analyze the methods to prevent consumtive behaviour. Total population of fishermen communities in Panai Hilir district are 2433 people and sample were determined to 100 persons by using purposive sampling. Data was collected through interviewing, documentation, observation and questionnaires. The conclusion of that study shows that more than 70% of fishermen communities in the district of Panai Hilir had consumptive lifestyle. Their consumptive lifestyles were like impulsive buying and non-rational buying. It occured due of low education level in fishermen communities. Most of the fishermen communities in the district of Panai Hilir are in the productive age, increasing number of average revenue in the district Panai Hilir, and access of information from highly technology communication devices. Consumptive lifestyle like this can be changed by improve the education of fishing communities, giving regulary counseling of financial managemet, avoiding and fortify themselves against the new product from the advertisements in electronic media and print media.Keywords : Fishermen Communities , Lifestyle , Consumtive , Consumtive type